PEMBERDAYAAN IBU HAMIL MELALUI PROGRAM EDUGIZI SEBAGAI UPAYA PENCEGAHAN KURANG ENERGI KRONIS (KEK) - Harna, Harna; Prita Dhyani Swamilaksita; Mira Asmirajanti; Asti Puji Lestari; Siti Fatimah Zahra; Venicia Eflin; Andi Muh Asrul Irawan (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
This community service activity was conducted with a focus on enhancing nutritional education for pregnant women in Lumpang Village, Parung Panjang Subdistrict, Bogor Regency, with the aim of preventing Chronic Energy Deficiency (CED). The education was delivered through a pocketbook titled "Healthy Pregnant Women Free from Chronic Energy Deficiency". The primary objective of this activity was to increase the understanding of pregnant women about the importance of adequate nutrition and the negative impact of chronic energy deficiency on maternal health and fetal development. The educational method used was designed to provide comprehensive knowledge to pregnant women about nutrition and CED prevention strategies. The results from the implementation of this method showed a significant increase in knowledge about CED among pregnant women. Moreover, the knowledge obtained could also be shared within their community, thereby allowing its impact to spread broadly among the population. The conclusion drawn from this community service activity is that the educational approach is an effective method to increase the knowledge and awareness of the community regarding the importance of nutrition and health during pregnancy.